Effect of induced interference and the formation of spatial perturbation fine structure in nonequlibrium open-ended system - Kuklin, V.M. (Вопросы атомной науки и техники, 2006)
It is shown, that the modes of unstable spectrum of instability near threshold are able to form long-living spatial fine structure and anomalous interference splashes, induced by the pump.